2013
DOI: 10.1016/j.biomaterials.2013.01.092
|View full text |Cite
|
Sign up to set email alerts
|

The antagonistic roles of PDGF and integrin αvβ3 in regulating ROS production at focal adhesions

Abstract: Reactive oxygen species (ROS) have been shown to play crucial roles in regulating various cellular functions, e.g. focal adhesion (FA) dynamics and cell migration upon growth factor stimulation. However, it is not clear how ROS are regulated at subcellular FA sites to impact cell migration. We have developed a biosensor capable of monitoring ROS production at FA sites in live cells with high sensitivity and specificity, utilizing fluorescence resonance energy transfer (FRET). The results revealed that platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…FA‐dependent production of ROS after response to growth factors (a Rac1‐dependent process) is limited by an α V β 3 /RhoA stimulation after adhesion on fibronectin (51). In line with these regulations, we can speculate that the reduction of FA along with the diminution of fibronectin deposition (as presented in this report) is associated with reduced α V β 3 /RhoA signaling.…”
Section: Discussionmentioning
confidence: 99%
“…FA‐dependent production of ROS after response to growth factors (a Rac1‐dependent process) is limited by an α V β 3 /RhoA stimulation after adhesion on fibronectin (51). In line with these regulations, we can speculate that the reduction of FA along with the diminution of fibronectin deposition (as presented in this report) is associated with reduced α V β 3 /RhoA signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, these data have been corroborated by live cell imaging of fibroblasts, in which a fluorescent redox probe was directed to focal adhesions via a paxillin tag. Thereby, it was demonstrated that a plateletderived growth factor (PDGF)-elicited ROS signal is reduced in aVb3 integrin-containing focal adhesions of fibroblasts attached onto fibronectin (94). Leukocytes are also well-known for their capacity to release substantial amounts of ROS, especially in the respiratory burst, while they attack pathogens (28,125).…”
Section: Eble and De Rezendementioning
confidence: 99%
“…Some ROS-regulated proteins were identified to play key roles in epithelial-mesenchymal transition and tumor metastasis. Integrin family members are of those ROS-regulated proteins [ 13 , 14 ]. Integrins are heterodimeric cell surface glycoproteins consisting of α and β subunits and control the attachment of cells to the extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%